Neurofibromatosis Type 2: A Pandora’s Box of Variable Presentations - Ashok Gandhi; Swarup Sohan Gandhi; Surendra Jain; Shashikant Jain; Paresh Sukhani (Indian Journal of Neurosurgery)
Introduction Neurofibromatosis type 2 (NF2) also known as MISME syndrome stands for multiple inherited schwannomas, meningiomas, and ependymomas in the peripheral and central nervous system. It is a rare disorder of autosomal dominant inheritance due to mutations of a tumor-suppressor gene on the chromosome 22q12. Clinically, it is characterized by multiple benign tumors arising in both the central and peripheral nervous system, particularly from the bilateral vestibular nerve, in more than 90% of the patients, with more than two thirds of them developing spinal tumors. Materials and Methods Here, we studied the variable presentations of cases of NF2, and thorough evaluation of patients was done by contrast MRI of brain and spine. Also, evaluation of ocular manifestations and cutaneous features was done in cases of NF2, and a follow-up was done for a period of 18 months with monitoring of cranial and spinal lesions. Conclusion We studied the various presentations of NF2 and found that a significant proportion of the patients presented with nonvestibular tumors as the initial presentation, with bilateral cerebellopontine angle lesions being an incidental finding; also, the age of presentation in half of the patients was less than 30 years, and so we can conclude that in young patients with spinal tumors or multiple meningiomas, a thorough evaluation regarding family history and various features of NF2 should be done, so that early identification of the disease could be done and patients can be benefitted from timely interventions.